Effects of weather scenarios and fertilizer on maize growth and yield: Insights from a greenhouse experiment - Souand P G Tahi; Kolawolé Valère Salako; Vinasetan Ratheil Houndji; Romain Glèlè Kakaï (PLoS ONE, 2025)
Maize is a major crop for food security, but its cultivation is threatened by climate change. Climate may affect the response of maize to fertilizer. This study examined the impact of weather parameters in combination with fertilizer types on maize growth and yield parameters in Benin. The experiment involved two sets of climatic scenarios. Scenario 1 (weather 1) had a moderate range of minimum and maximum temperatures and maximum humidity suitable for maize cultivation in Benin. Scenario 2 (Weather 2) featured a broader range of parameter values below and above those of Weather 1. Five types of fertilizers were tested: Organic (Cow dung), Chemical (NPK), Intermediate 1 (mixture of high NPK and low Cow dung), Intermediate 2 (mixture of middle NPK and middle cow dung), and Intermediate 3 (mixture of high cow dung and low NPK). These factors were combined in a split-plot design and data were collected on maize germination, growth, and yield variables. Models such as DNNsurv, Cox, linear mixed effect, and decision trees were used for data analysis. Results revealed that maize seeds had a higher probability of germination between 2 to 5 days after sowing, with over 80% of the seeds germinating the fifth day. Intermediate 1 and organic fertilizers were particularly effective in promoting maize growth, resulting in larger diameters and heights. Organic, chemical, and intermediate 1 fertilizers led to higher yields under weather scenario 2, while intermediate 3 and organic led to higher yields under weather 1, suggesting that organic fertilizers could be more sustainable and cost-effective than mineral fertilizers. Additionally, Weather 2 was associated with higher maize yields suggesting that, a relatively broader range of climate parameters would positively affect maize yield. These findings can assist farmers and policymakers in making well-informed decisions regarding the most suitable fertilizers to use under various weather conditions, maximizing their yield and profits.